Fitting places in knowledge translation: Biomedical innovation in healthcare practice. Issue 10 (October 2021) - Foord, David
Highlights: Researchers are fundamental contributors to biomedical knowledge and innovation in healthcare practice. Researchers contributed through both basic and integrated (IKT) models of knowledge translation. Basic knowledge translation preceded IKT in biomedical engineering device development. The transition to IKT was accompanied by changing understandings about research practice. Fitting places provided contexts for discussions and confrontations among researchers and stakeholders. Abstract: The purpose of this study is to examine and further develop knowledge translation in the context of a biomedical device industry. Studies have yet to explain how science-based innovation is first reduced to practice in development of new biomedical technologies. To understand how this occurs, I investigated research and commercial product development in the powered prosthetic arm industry from 1945 to 2020. The findings demonstrate the foundational roles of basic knowledge translation in the production of new knowledge for the powered upper limb industry, and integrated knowledge translation in hospital and clinic-based development of powered hands. The focus on a biomedical engineering industry limits the generalizability of the findings. Future research directions include examination of other cases to identify practices in embedding research projects in locations-of-use as well as virtual fitting spaces.